Creative Tourism for Cultural Preservation: A Bibliometric Review - Loso Judijanto; Sumarni Sumarni (Westscience Press, 2026)
This study presents a bibliometric analysis of research on creative tourism and cultural preservation to map its intellectual structure, thematic evolution, and collaborative patterns. Using a comprehensive dataset retrieved from an academic database and analyzed through VOSviewer, the study applies co-occurrence, citation, density, and network visualization techniques to identify dominant research themes and their interrelationships. The findings reveal that the intellectual core of the field is primarily structured around tourism, historic preservation, sustainable development, and cultural heritage, indicating a strong sustainability-oriented foundation. Cluster analysis further demonstrates the integration of cultural preservation with rural development, heritage management, and cultural industries, while emerging themes such as digital heritage technologies—including augmented reality, virtual reality, and artificial intelligence—reflect a gradual transformation toward technology-enhanced tourism experiences. The citation analysis identifies highly influential works spanning cultural theory, rural heritage systems, and digital preservation strategies, highlighting the interdisciplinary nature of the field. Meanwhile, co-authorship and country-level network analyses indicate strong but uneven collaboration patterns, with a small number of central actors and countries serving as key bridges in global research dissemination.